2020
DOI: 10.1186/s13071-020-04229-5
|View full text |Cite
|
Sign up to set email alerts
|

Eimeria tenella Eimeria-specific protein that interacts with apical membrane antigen 1 (EtAMA1) is involved in host cell invasion

Abstract: Background: Avian coccidiosis is a widespread, economically significant disease of poultry, caused by several Eimeria species. These parasites have complex and diverse life-cycles that require invasion of their host cells. This is mediated by various proteins secreted from apical secretory organelles. Apical membrane antigen 1 (AMA1), which is released from micronemes and is conserved across all apicomplexans, plays a central role in the host cell invasion. In a previous study, some putative EtAMA1-interacting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…At 48 h pi, EteIF-5A was mainly localized in the cytoplasm of immature schizonts, and fluorescence was weaker (Figure 8E and Supplementary Figure 3). At 72 h pi, EteIF-5A was mainly localized in the cytoplasm of mature schizonts (Li C. et al, 2020), and fluorescence was stronger than at 48 h pi (Figure 8F).…”
Section: Localization Of Eteif-5a By Immunofluorescencementioning
confidence: 97%
“…At 48 h pi, EteIF-5A was mainly localized in the cytoplasm of immature schizonts, and fluorescence was weaker (Figure 8E and Supplementary Figure 3). At 72 h pi, EteIF-5A was mainly localized in the cytoplasm of mature schizonts (Li C. et al, 2020), and fluorescence was stronger than at 48 h pi (Figure 8F).…”
Section: Localization Of Eteif-5a By Immunofluorescencementioning
confidence: 97%
“…By extension, MIC 1–5, 7–9 and apical membrane antigen (AMA) 1–2 have been identified in sporozoites of E. tenella [ 41 , 71 , 85 , 90 , 91 ] with several MIC and AMA orthologues [ 92 ]. Similarly, MIC 1, 2, 4, 5 and 7 and AMA 2 have been identified in E. tenella second-generation merozoites [ 93 ].…”
Section: Apical Complex Proteinsmentioning
confidence: 99%
“…However, ESP is a non-micronemal protein expressed on the surface of permeabilised sporozoites, sporocysts and second-generation merozoites of E. tenella (Table 1 ). Using glutathione S-transferase fusion protein pull-down and bimolecular fluorescence complementation assays, ESP was shown to directly interact with AMA1 of E. tenella to mediate sporozoite invasion [ 92 ] but the regulatory, phenotypic and genetic consequences of AMA1/ESP complex were not completely elucidated as authors only suggested post-translational modification of these proteins. Similarly, Eimeria -conserved protein (ECP) is specific to E. maxima , E. acervulina and E. tenella but its expression is most prominent in sporozoites of E. tenella [ 110 ].…”
Section: Proteins Associated With the Eimerian Apical Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of avian species E. tenella comprises approximately 60 Mbp DNA ( Shirley, 2000 ), with approximately 8,618 genes ( Cai et al, 2003 ). Over the past decades, several techniques such as immunofluorescence localization, recombinant proteins, Western blotting, RT-PCR, and protein pull-down assay have been used to delineate the function of genes for cell cycle ( Diallo et al, 2019 ), invasion ( Li et al, 2020a , b ), and drug resistance ( Yu et al, 2021 ). However, due to the lack of genome manipulation tools, the function of only a very few genes has been well deciphered ( Blake, 2015 ).…”
Section: Introductionmentioning
confidence: 99%